2022
DOI: 10.3389/fpsyt.2022.1081013
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic and the Russia-Ukraine war on stress and anxiety in students: A systematic review

Abstract: BackgroundThe outbreak of the COVID-19 pandemic at the end of 2019 and the Russian-Ukrainian war in February 2022 created restrictions and uncertainties that affected the general population’s mental health. One of the affected groups was students. This systematic review summarizes the current literature on the prevalence, outcomes, and interventions for stress and anxiety among university, college, graduate, or postsecondary populations.MethodsA systematic literature search was performed on PubMed, Web of Scie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
6

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 48 publications
0
18
0
6
Order By: Relevance
“…In particular, the proper diagnostics, identification, treatment and reporting of COVID-19 cases around Ukraine as well as implementation of prevention measures became challenging 94 . In addition to that, there were indications of increase in stress and anxiety 92,95 . There was also overwhelming pressure on the Ukrainian healthcare system due to war casualties, reduced access to primary medical treatment, damages to the socioeconomic system and many other factors 92 .…”
Section: Analysis Limitationsmentioning
confidence: 89%
“…In particular, the proper diagnostics, identification, treatment and reporting of COVID-19 cases around Ukraine as well as implementation of prevention measures became challenging 94 . In addition to that, there were indications of increase in stress and anxiety 92,95 . There was also overwhelming pressure on the Ukrainian healthcare system due to war casualties, reduced access to primary medical treatment, damages to the socioeconomic system and many other factors 92 .…”
Section: Analysis Limitationsmentioning
confidence: 89%
“…Moreover, Russia launched a large-scale military attack on Ukraine a few weeks before the start of the April 2022 survey. Limone et al [ 37 ] observed that stress and anxiety among students that were caused by the COVID-19 pandemic were additionally intensified by the Russian–Ukrainian war.…”
Section: Discussionmentioning
confidence: 99%
“…All of these factors may contribute to an increase in the number of psychoactive substance users who need mental health care. In addition, there is currently a war going on at Poland’s eastern border, which is certainly not without impact on the mental wellbeing of the region’s inhabitants [ 18 , 19 ]. It seems important to monitor the state of mental health in the group of psychoactive substance users and conduct further research to determine the exact causes of such a phenomenon, taking into account as many factors as possible that could cause such a sharp increase.…”
Section: Discussionmentioning
confidence: 99%